IMPLIKASI DISIPLIN KERJA, KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAPKINERJA KARYAWA (studi pada PT. Borobudur Oto Mobil Yogyakarta) - Eka indah sari (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
This study aims to analyze the effect of Work Discipline, Financial compensation and non-financial compensation to employees at PT. Borobudur Oto Mobil Yogyakarta. The nature of this study uses quantitative methods. Data collection is done by distributing questionnaires directly to the employees of PT. Borobudur Oto Mobil Yogyakarta, amounting to 60 people and the data is processed using SPSS software version 24. Analysis of this data uses validity, reliability, classical assumption, and multiple linear analysis. The results of the analysis concluded that the independent variable and the dependent variable have a significant positive relationship and simultaneous effect together